Morpho-functional basis of endothelial dysfunction in diabetes mellitus - A. I. Gozhenko; H. S. Kuznetsova; K. S. Kuznetsova; O. M. Kuznetsova; T. M. Byts; W. Zukow (Kazimierz Wielki University, 2017)
The diabetes mellitus (DM) inevitably progresses and leads to complications, among which the main place is occupied by micro- and macroangiopathies. The presence of endothelial damage in DM can be established even before macroscopically significant damage to the vessel. At the same time, there is no summary ED characteristic for diabetes. The aim of the study is to make a comprehensive evaluation of ED in DM -1 and DM-2 types. Materials and methods of research. 60 persons, including 53 DM type 1 and type 2, with a severe course (state of decompensation) participated in the present study. We used the method of estimating ED by the number of circulating desquamation endothelial cells (CECs) at the stages of decomposition with simultaneous determination of NO2- and NO3- metabolites of nitric oxide. Results and discussion. In patients with diabetes, the level of CECs increased in 3-5 times and ranged from 1800 to 11,200 cells / ml. The average amount of CECs in patients with diabetes was 3358.5 ± 366.3 cells / ml. Conclusions: Endothelium is involved in the pathological process at DM. This is evidenced by a significant increase in CECs in the blood plasma. The use of this method allows to detect ED before clinically considerable vascular impairment and reflects the severity of the course and duration of DM.